Pengaruh Harga, Lokasi dan Kualitas Pelayanan terhadap Keputusan Pembelian Produk Pertanian di Toko MitraTani Ds.Gelang Kab. Madiun - Kholip Antari; Baju Pramutoko; Dadang Afrianto (FEB Universitas Maritim Semarang, 2023)
There are factors such as price, location and service quality which greatly influence purchasing decisions. If these factors influence purchasing decisions, consumers tend to make repeat purchases. The aim of this research is to explain the partial and simultaneous influence of price, location and service quality on purchasing decisions for agricultural products at Mitra Tani Shop Ds.Gelang, Madiun Regency. This research uses quantitative methods with a population of 8,184 consumers using the Accidental Sampling technique. The calculation results from the Slovin formula obtained a sample of 99 respondents. Data processing uses the SPSS program. The results of this research show that the variables Price, Location and Service Quality have a significant simultaneous effect on purchasing decisions for agricultural products at Mitra Tani Shop Ds.Gelang, Madiun Regency.